Education Of Life dalam Fenomena Perkawinan Suku Sasak - Muhamad Yusuf Al-Hamdani (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2019)
One of a series in the customs marriage the community of sasak pengembur village is merarik, that is an agreement between men and women to marry. In the tradition of marriage nobleman a girl brought run first from power their parents before a wedding procession according to tradition and religion be held. Away referred to as the beginning of the act of implementing the marriage. Thus, marriage to the community of sasak more popular with the term sasak called “merarik”. In conception culture merarik, merarik provide opportunities for men and women to determine a spouse. This study aims to reveal the aristocratic tradition of marriage gender perspective, with a focus on : (1) the tradition of marriage nobility (2) gender equity in the tradition of marriage nobility (3) gender inequality in the tradition of aristocratic marriage, which is performed in the Pengembur village. This study adopted qualitative approaches kind of fenomenologis. Technique data collection was carried out by interviews, participatory observation, and documentation. Technique data analysis covering reduction data, presentation of data and the withdrawal of conclusion. Checking the validity of data was undertaken by means of extra participation researchers, technique triangulation, discussion companion, checking members. The results showed that (1) the tradition of marriage conducted in the Pengembur village is by way of a girl running from the power of parents in terms Sasak called merarik (2) gender equity in the tradition of marriage nobility there are no symptoms of discrimination on their voting rights in determining couples to marry because, the concept of culture merarik provide equal opportunities between women and men. (3) gender inequality in the tradition of aristocratic marriage discrimination is symptomatic that when aristocratic women married to men not noble, then the woman would be in waste that puts on marginal and subordinate position.